On tides in estuaries and around small islands - Yih, Chia-Shun, author; American Geophysical Union, publisher (Colorado State University. Libraries, 1953)
Tides in estuaries and around small is lands are studied in this paper. Under the assumption that the width and the mean depth of the estuary can be adequately expressed as power functions of the longitudinal distance from a certain point upstream, and that the depth of the ocean varies as a power function of the radial distance from the island, analytical solutions can be found by very simple transformations.
Reprint from Transactions, American Geophysical Union, V. 34, Number 3, June 1953.
CER53CSY13.
Keywords: Tides; Estuaries